Rare bird documentation form for Greater Scaup at Pleasant Creek Lake, 1996 - Dankert, Jeffrey B.et al (1996)
Rare bird documentation form for two Greater Scaups at Pleasant Creek Lake in Linn County, IA on March 17, 1996. Epson - sheet feed